Pengaruh Pengetahuan Peraturan, Ketidakpastian Lingkungan Dan Penggunaan E-Procurement Terhadap Tingkat Penyerapan Anggaran Pengadaan Barang Dan Jasa Pada Pemerintah Daerah Kabupaten Badung - Ni Putu Ayu Amanda Putri; Edy Sujana (Universitas Pendidikan Ganesha, 2022)
This study was conducted to determine the effect of regulatory knowledge, environmental uncertainty and the use of e-procurement on the level of absorption of the budget for the procurement of goods and services.. The population in this study is LPSE in Badung Regency. The sample selection was carried out using the saturated sample technique, so the sample in this study was the employees of the LPSE for the procurement of goods and services, totaling 60 employees. Data were collected through questionnaires, then carried out several data analysis such as data quality test, classical assumption test which includes normality test, multicollinearity test and heteroscedasticity test and multiple linear regression test which includes t test and coefficient of determination test. Based on the data quality test, the data was declared valid and reliable. The classical assumption test states that the data is normally distributed, free from multicollinearity symptoms and free from heteroscedasticity symptoms. In this study, the significance of the regulatory knowledge variable was 0.021, the environmental uncertainty variable was 0.022, and the e-procurement use variable was 0.009 (<0.05). Then it shows that the regulatory knowledge variable (X1), environmental uncertainty (X2) and the use of e-procurement (X3) each can affect the level of budget absorption.